"I don't think I have a chance to get it": International university student HPV knowledge and preventive behaviors. Issue 1 (14th February 2022) - Nkwonta, Chigozie A.; Dawson, Robin M.; Adegboyega, Adebola
Abstract: Objective: Half of new human papilloma virus ( (HPV)) infections occur between the ages of 15 and 24. As preventive measures are underutilized globally; international university students are at particular risk for HPV infection and sequelae. The study aim was to explore HPV knowledge and preventive behaviors in this population. Participants: Eighty-one undergraduate and graduate international university students (49 females, 32 males) at a southeastern university. Methods: Exploratory sequential mixed methods guided by the Health Belief Model. Results: Integrated qualitative/quantitative data revealed four themes mapped to relevant HBM constructs: Perceived susceptibility to HPV ; Perceived benefits/Perceived barriers to HPV prevention; Cues to Action; and Likelihood of Engaging in Health-Promoting Behavior. Over half believed they were not at risk for HPV/sequelae. Only a quarter had received HPV vaccination. Conclusions: International university students represent an important catch-up population for HPV screening/vaccination. Results can be used to design and tailor interventions for this vulnerable population.